METODE PELAKSANAAN PONDASI BORE PILE PADA PEKERJAAN DINDING PENAHAN TANAH PENANGANAN LONGSORAN PROYEK PRESERVASI JALAN BTS. KOTA SUMEDANG – CIJELAG KM. BDG 70 + 100 - Firmansyah, Rendy Rizkyta; Kholiq, Abdul (Universitas Majalengka, 2025)
The implementation of bore pile foundations on the Cirebon Palimanan Sumedang KM. BDG. 70 + 100 Sumedang Regency road preservation project is one of the landslide handling work items that aims to strengthen the retaining wall structure, where the retaining wall structure that was built, because the new retaining wall had to be built because the previous existing condition had collapsed. The foundation for building a retaining wall uses a borepile foundation, which is a type of deep foundation. The installation method is to first use a large borepile machine to drill the soil with a certain diameter on the soil until it reaches the specified depth, then install the assembled steel rods. Frame and insert it into the drill hole, then insert it into the drill hole. The purpose of implementing this practical work is to understand the implementation of field construction, especially in road preservation projects, to understand the Bore Pile foundation work process in retaining wall construction, especially in handling landslides. In the method of implementing bore pile foundations in the landslide handling work of the Cirebon - Palimanan Sumedang road preservation project, there are several stages of work including preparation work, reinforcement work, drilling work, bore pile casting work, and Test Pile work.